Analisa Status Mutu Air Dan Daya Tampung Beban Pencemaran Sungai Wanggu Kota Kendari - Sahabuddin, Hartina; Harisuseno, Donny; Yuliani, Emma (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
This study aims to determine the water quality in the Wanggu river of the upstream, midstream and downstream . Decrease quality of water in the Wanggu river each year has increased due to changes over the function in using land until occur of water pollution.The study was conducted in April and May 2013, the measurement of water quality in the River Wanggu there are 10 parameters in measuring the temperature , TDS , TSS , pH , BOD , COD , DO , Nitrate , Nitrite and Mn and also uses secondary data . Parameters TDS , TSS , COD and BOD are increasing every year. The status of water quality in the Wanggu river was Determined by using the method of STORET, Wanggu river has been heavily polluted and Pollution Index method had moderately polluted. For the calculation of Pollution Load Capacity in Wanggu river does not have the capacity anymore to increase the BOD parameters required water pollution control strategies. Wanggu river as a potential source of raw water can be used as a clean water source for the future of kendari city residentsKeywords: Water quality,, Methods STORET, Pollution Index Method, Pollution Load Capacity.